2018
DOI: 10.1016/j.jri.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Microglia, the missing link in maternal immune activation and fetal neurodevelopment; and a possible link in preeclampsia and disturbed neurodevelopment?

Abstract: Disturbances in fetal neurodevelopment have extensively been related to neurodevelopmental disorders in early and later life. Fetal neurodevelopment is dependent on adequate functioning of the fetal immune system. During pregnancy, the maternal immune system is challenged to both tolerate the semi-allogenic fetus and to protect the mother and fetus from microbes. The fetal immune system is influenced by maternal immune disturbances; therefore, perturbations in maternal immunity likely do not only alter pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 61 publications
0
47
0
Order By: Relevance
“…It is also known that various cytokines, as well as maternal leukocytes, cross the placental barrier [88]. The recent outbreak of Zika virus (ZIKV) infection in Brazil revealed a series of devastating consequences on fetal neurodevelopment that exemplifies how an environmental component like a virus can cause abnormal neurodevelopment, affecting the fetus's immune system, possibly through changes in the maternal immune function, placental function, and microglia activity [89]. In the same vein, it has been postulated that during maternal infection, fetal microglia can be directly activated by some viruses, or indirectly through cytokines or microchimeric maternal cells [88].…”
Section: Neuroinflammation and Microglial Function In Infectious Condmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that various cytokines, as well as maternal leukocytes, cross the placental barrier [88]. The recent outbreak of Zika virus (ZIKV) infection in Brazil revealed a series of devastating consequences on fetal neurodevelopment that exemplifies how an environmental component like a virus can cause abnormal neurodevelopment, affecting the fetus's immune system, possibly through changes in the maternal immune function, placental function, and microglia activity [89]. In the same vein, it has been postulated that during maternal infection, fetal microglia can be directly activated by some viruses, or indirectly through cytokines or microchimeric maternal cells [88].…”
Section: Neuroinflammation and Microglial Function In Infectious Condmentioning
confidence: 99%
“…Moreover, it has been shown that ZIKV invades microglial cells, promoting inflammation, thus disrupting their physiological role during brain development [90]. In addition to ZIKV, other viruses such as cytomegalovirus (CMV) and Rubella also cross the placental barrier and/or BBB and reach the CNS [89]. CMV infection of newborn mice induces a strong inflammatory response in the brain, characterized by microglial activation, recruitment of peripheral immune cells, and the expression of pro-inflammatory cytokines [91].…”
Section: Neuroinflammation and Microglial Function In Infectious Condmentioning
confidence: 99%
“…In mammals, maternal immune activation, or MIA, which can be due to an inflammatory stimulus like bacterial or viral infections but also activated after allergy during the pregnancy, has been shown to positively correlates with the risk of developing neuropsychiatric disorders like autism in the offspring ( Vogel Ciernia et al, 2018 ). This link may be bridged to an impact of MIA on the microglia from the fetus which leads to the acquisition of functional changes that are maintained in the adult ( Mattei et al, 2017 ; Prins et al, 2018 ; Figure 2D ). In a majority of animal models of maternal immune activation, the rat dams or pregnant mice are treated with either a viral mimetic (poly I:C) or LPS.…”
Section: Perspectivesmentioning
confidence: 99%
“…The activity of microglia is affected by the maternal immune system and could be activated by a pro‐inflammatory fetal state (Boksa, ; Prins et al. ), leading to an increase in microglial cell number and distribution, as well as their altered morphology. We aimed to limit this effect by selecting samples with no macro‐ or micro‐morphological anomalies, and only fetuses and premature infants with normal prenatal courses up to abortion or premature birth.…”
Section: Discussionmentioning
confidence: 99%